ART GALLERY IN PALANGKA RAYA - Perkasa, Petrisly (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The enactment of Law No. 22 of 1999 on Regional Autonomy, which every district / municipality is required to utilize the full potential of the region in order to achieve development targets are not only limited in an effort to increase revenue (PAD), but also efforts to more tangible, namely to improve the welfare of society and one of them is the wealth of art and culture of Central Kalimantan developed as a basis for the tourism development. Central Kalimantan Province has the potential, sources of inspiration and sufficient raw materials in the art works but having problems in the development of them, artists do not have a representative place to introduce and sell the artwork. To introduce an art a facility is needed, that has the function to organize the work of art as well as marketing products and Central Kalimantan province, especially the town of Palangkaraya in dire need of such planning. Art gallery is the right solution for the planning because the gallery can be defined as a room or building that is managed by a permanent institution, serves to collect, preserve, exhibit and sale of works of art.